2023
DOI: 10.1177/20503121221150101
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of healthcare workers toward advanced cardiac life support in Felege Hiwot Referral Hospital, Bahir Dar, Ethiopia, 2022

Abstract: Objective: The aim of this study was to investigate the knowledge and attitude regarding advanced cardiac life support among healthcare workers, 2022. Methods: A cross-sectional study was conducted from March to May 2022 among healthcare workers who were working in Felege Hiwot Comprehensive Specialized Hospital Bahir Dar, Ethiopia. All physicians and nurses who were willing to participate this study were involved. A structured self-administered questionnaire was used for data collection. The data were entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This finding is surprising because Adal and Emishaw reported higher ALS knowledge levels among physicians working in the emergency department for 10 years or more. 26 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is surprising because Adal and Emishaw reported higher ALS knowledge levels among physicians working in the emergency department for 10 years or more. 26 …”
Section: Discussionmentioning
confidence: 99%
“…A study found that only 12% of healthcare workers had adequate knowledge of basic life support (Chaudhary et al, 2023). Most healthcare workers, especially nurses, require improvement in their knowledge of basic life support (Adal & Emishaw, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In Addis Ababa city, there are more than 53 hospitals, of which 13 are public hospitals and more than 40 are private hospitals. 16 - 18 The study population contained all nurses who were working in 5 randomly selected public hospitals in Addis Ababa city.…”
Section: Methodsmentioning
confidence: 99%